GEOMECHANICAL ANALYSIS ON BASEMENT IN SUBAN FIELD, SOUTH SUMATRA BASIN - BURHAN, NURUL
Suban field is the largest gas field which has a reservoir in basement. Basement reservoir connected to sediments reservoir that lie on top of it. Basement and sedimentary formations in these field are formed by geology compressional structure. These geological event is believed to form fractures in basement that has sufficient porosity for a reservoir. However, the problem to be analysed is whether the current stress state in the field is still compressional (shear fault and reverse fault regime) or in slightly compressional (shear faults and normal faults regime) or even extensional (normal fault regime). Generally there are consistent relationship between regime stress with structural geology in some areas. There are anomalies relationship such as in Tampen spur (North Sea) which has a compressional regime while the geological structure show the extensional area (normal faults). Compressional stress regime was formed by reactivation of normal faults and uplift in the last 20.000 years. The incident occurred in the basin opposite Monagas (Venezuela). Geological structure of the area is very compressional form of reverse fault regime, however the stress that work on the state slightly compressional (shear faults stess regime and normal fault regime). Geomechanics method is one method that can be applied to find out the current stress state on basement. This method is an integration of three principal stress, (Sv, SHmax, Shmin), pore pressure (Pp), and rock strength (C0). These parameters was obtained through a variety methods during and after drilling processes such as: vertical stress (Sv) obtained from log density, pore pressure determined by direct measurement from the DST or RFT, minimum horizontal stress (Shmin) using the available LOT and xLOT data, rock core test condacted to measured the rock strength. Direction of maximum horizontal stress (SHmax) is obtained from observations of breakout and drilling-induced tensile fractures on image logs, while magnitude of maximum horizontal stress is obtained through modeling based on breakout and drilling-induced tensile fractures features. Each of parameters that build geomechanical model has it’s own uncertaintly, due to lack of tools, lack of data, and lack of knowledge to analysis the data. So these uncertainly should be considered in taking assumptions and explanations about the level of confidence in each parameter in order to build the geomechanics models. Information regarding magnitude of three principal stress: Sv (vertical stress), Shmin (minimum horizontal stress), and SHmax (maximum horizontal stress), is used to classify the insitu stress regime in each well based on Anderson's classification: normal faults (Sv > SHmax > Shmin), Strike-slip regime (SHmax > Sv > Shmin), or reverse fault regime (SHmax > Shmin > Sv). Analysis stress on bedrock in the study area indicates that the area of research is the compressional strees condition (shear fault regime and reverse fault). This condition is consistent with the geological compressional structures in the study area. In this stress SHmax regime serves as the biggest strees (S1), serves as smallest stress Shmin (S3) located in well B-1, B-2, B-4, B-5, B-6 and B-8 (regime fault shear), while acting as smallest stress Sv (S3) located in well B-3 and B-7 (reverse fault regime). The observation log images indicate that there are two-way maximum horizontal stress to the direction of the breakout and fracture-induced tensile. Maximum horizontal stress tends towards northeast - southwest (NE - SW) located in well B-2, B-3, B- 6, and B-8 whereas in well B-1, B-4, B-5 and B-7 shows the direction of the maximum horizontal stress tends to the northwest - southeast (NW - SE). Based on regional data, the direction of maximum horizontal stress (?) in Sumatra is N 15 ° E, while the direction of maximum shortening in the study area based on seismic data is the northeast - southwest (N 45 ° E). Directions stress SHmax the north northeast - south southwest (NNE - SSW) in well B-2 and B-3 occurs due to regional direction of maximum horizontal stress, while the direction of SHmax stress toward northeast - southwest in well B-6 and B-8 occurs in the direction of maximum shortening or compressional direction (?c) maximum horizontal stress. Well B-7, the SHmax stress a northerly trending to north northwest - south southeast (NNW - SSE) can be described mechanically as a result of regional stress but changed direction due to a turned fault plane. Well B-1, B-4 and B-5 can be described by the principle of mechanics. All of these wells SHmax stress direction are parallel to the fault direction in northwest - southeast (NW - SE) and perpendicular to the direction of maximum shortening and without any influence of the fault plane. This is most likely occurs due to the anisotropy of rocks in field or rotation stress.